Graded crystalline HfO gate dielectric layer for high-k/Ge MOS gate stack - Lee, Chan Ho; Yang, Jeong Yong; Heo, Junseok; Yoo, Geonwook (IEEE Journal of the Electron Devices Society, 2021)
Germanium (Ge) has gained great attention not only for future nanoelectronics but for back-end of line (BEOL) compatible monolithic three-dimensional (M3D) integration recently. For high performance and low power devices, various high-k oxide/Ge gate stacks including ferroelectric oxides have been investigated. Here, we demonstrate atomic layer deposited (ALD) polycrystalline (p-) HfO2/GeOX/Ge stack with an amorphous (a-) HfO2 capping layer. The consecutively deposited a-HfO2 capping layer improves hysteretic behaviors (ΔV) and interface state density (Dit) of the p-HfO2/GeOX/Ge stack. Furthermore, leakage current density (J) is significantly reduced (× 100) by passivating leakage paths through grain boundaries of p-HfO2. The proposed HfO2 layer with the graded crystallinity suggests possible high-k/Ge stacks for further optimized Ge MOS structures.
Keywords: Atomic layer deposited; Back end of lines; Crystalline HfO2; Ferroelectric oxides; Hysteretic behavior; Interface state density; Low-power devices; Polycrystalline; ALD HfO2; amorphous; Ge; leakage; polycrystalline